PENGARUH CAR, NPL, DER, BOPO DAN LDR TERHADAP ROE PADA PERUSAHAAN DAERAH BANK PERKREDITAN RAKYAT BANK PASAR DI JAWA TENGAH TAHUN 2011 - 2013 (Students' Journal of Accounting and Banking, 2015)
Resulted in the rapid development of rural bank stiff competition among fellow rural bank or other financial institutions. Therefore, rural bank is required to have a business that is economical, effective and efficient. One of the elements that are all concerned to know whether an efficient can be seen from the level of health, where its application can be seen on the profitability (ROE). This study examined the effect of variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Debt to Equity Ratio (DER), Operating Ratio (OR) and Loan to Deposit Ratio (LDR) simultaneously and partially on profitability (ROE). This research was conducted at government rural bank at Central Java 2011 – 2013. Observation made in 22 rural banks for 3 years so getting 66 observation. To examined the sample used multiple linear regression. F-test results indicate that the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Debt to Equity Ratio (DER), Operating Ratio (OR) , Loan to Deposit Ratio (LDR) and simultaneously significant effect on profitability in government rural bank. T-test result showed that Debt to Equity Ratio (DER) and a significant positif effect on profitability (ROE), Non Performing Loan (NPL) not significant positif effect on profitability (ROE), but Capital Adequacy Ratio (CAR), Operating Ratio (OR) and Loan to Deposit Ratio (LDR) and significant negative effect on profitability (ROE).Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Debt to Equity Ratio (DER), Operating Ratio (OR), Loan to Deposit Ratio (LDR) and Return On Equity (ROE)